Access to health care for uninsured Latina immigrants in South Carolina - John S. Luque; Grace Soulen; Caroline B. Davila; Kathleen Cartmell (BMC, 2018)
Abstract Background South Carolina is considered a "new destination" state for Latino immigrants. Language barriers, transportation difficulties, low socioeconomic status, inflexible work schedules, different cultural norms, and anxiety and fear related to the current anti-immigrant political climate all negatively impact Latino immigrants' frequency of contact with the health care system, and consequently they suffer poor health outcomes. The study objective was to explore uninsured Latina immigrant women's access to health care and alternative treatment strategies in coastal South Carolina. Methods The study design was a qualitative interview design. Thirty women participated in semi-structured interviews in community sites. Thematic analysis identified salient categories of topics across interview participants. Results The themes were organized into four primary categories including: 1) Barriers and Facilitators to Healthcare, 2) Health Behaviors and Coping Mechanisms, 3) Disease Management Strategies, and 4) Cultural Factors. Participants demonstrated determination for accessing care but reported that their primary health care access barriers included the high cost of services, lack of health insurance, family and work responsibilities, and language barriers. Coping mechanisms included activating their social networks, visiting family and friends and assisting one another with navigating life challenges. Conclusion Participants overcame obstacles to obtain healthcare for themselves and their family members despite the multiple barriers presented. Social networks were leveraged to protect against some of the negative effects of financial barriers to health care access.